“Caminando Con Riesgo”: perceptions of occupational injury, workplace safety and workers rights among Spanish-speaking hospitalized patients - Zeidan, Amy; Cortes, Juliana; Marcovitch, Hannah; Chicas, Roxana; Smith, Randi N.; Stevens, Alessandra; Zambrana, Elizabeth; Anand, Shelly (Frontiers in Public Health, 2024)
Introduction: Occupational health disparities are well documented among immigrant populations and occupational injury remains a high cause of morbidity and mortality among immigrant populations. There are several factors that contribute to the high prevalence of work-related injury among this population and those without legal status are more likely to experience abusive labor practices that can lead to injury. While the work-related injuries and experiences of Spanish-speaking workers have been explored previously, there is a paucity of literature documenting injury among hospitalized patients. Additionally, there are few documented hospital-based occupational injury prevention programs and no programs that implement workers rights information. The purpose of this study was to further explore the context of work related injuries primarily experienced by Spanish speaking patients and knowledge of their rights in the workplace. Methods: We conducted four semi-structured qualitative interviews with Spanish speaking patients admitted to the hospital for work related injuries. The study team member conducting interviews was bilingual and trained in qualitative methodology. An interview guide was utilized for all interviews and was developed with an immigrant workers rights organization and study team expertise, and factors documented in the literature. Participants were asked about the type and context of the injury sustained, access and perceptions of workplace safety, and knowledge of participants rights as workers. All interviews were conducted in Spanish, recorded, transcribed in Spanish and then translated into English. A codebook was developed and refined iteratively and two independent coders coded all English transcripts using Dedoose. Interviews will